What Heraclitus and Parmenides have in common on Reality and Deception - Bossi, Beatriz (Logos. Anales del Seminario de Metafísica, 2015)
It is usually assumed that Heraclitus is, exclusively, the philosopher of flux, diversity and opposition while Parmenides puts the case for unity and changelessness. However, there is a significant common understanding of things (though in differing contexts), not simply an accidental similarity of understanding. Both philosophers, critically, distinguish two realms: on the one hand, there is the one, common realm, identical for all, which is grasped by the ‘logos that is common’(Heraclitus) or the steady nous (Parmenides) that follows a right method in order to interpret the real. On the other hand, the realm of multiplicity seen and heard by the senses, when interpreted by ‘barbarian souls’, is not understood in its common unity. Analogously, when grasped by the wandering weak nous it does not comprehend the real’s basic unity. In this paper I attempt to defend the thesis that both thinkers claim that the common logos (to put it in Heraclitean terms) or the steady intellect (to say it with Parmenides) grasp and affirm the unity of the real.